Anti-hairloss efficacy of coffee berry extract - Prinyarux, Thanon; Saewan, Nisakorn (Food and Applied Bioscience Journal, 2020)
An important enzyme causing hair loss in human is 5−alpha−reductase by catalyzing the conversion of testosterone to dihydrotestosterone (DHT) which induced miniaturization of the hair follicle. Coffee berry is a natural source of caffeine and chlorogenic acid which shows inhibition of the enzyme activity. The objective of this research was to determine the total phenolic content, DPPH radical scavenging and inhibition of 5−alpha reductase activities of coffee berry extract and evaluate anti−hair loss efficacy of tonic containing the extract on 47 volunteers. Coffee berry extract showed high quantity of caffeine 0.43 mg/mL by HPLC technique. The total phenolic content was found to be 0.73 ± 0.02 mg GAE/mL extract. The DPPH radical scavenging of the extract showed the IC50 value of 4.10 ± 0.29 mg/mL. The cytotoxicity and 5−alpha−reductase inhibition of the extracts were investigated on prostate cancer cell lines (DU−145). The cell viability of coffee berry extract at concentration 0.1, 1, 10, 100 and 1,000 µg/mL showed 102.8, 97.6, 91.8, 97.7 and 88.8%, respectively, which indicating that the extract has not cytotoxic on the cell lines. The coffee berry extract at 1,000 µg/mL was selected to evaluate 5−alpha−reductase inhibition. The extract showed slightly lower inhibition of 5−alpha−reductase activity with 16.5% than the standards, finasteride (32.5%) and dutasteride (20.1%). In clinical trial, 13 male and 34 female volunteers who have hair loss problem were selected and divided randomly into two groups. First group applied placebo spray tonic (C) and the second group applied spray tonic containing 10% coffee berry extract (CB) everyday for 12 weeks. The volunteers were assessed for hair loss reduction by one−minute combing test every month. The CB group showed significant reduction in the mean number of hairs loss after combing test from 11.5 to 2.4, 1.9 and 1.4 (P<0.01) for 1, 2 and 3 months, respectively. The CB group showed better efficacy for hair loss reducing than placebo. In conclusion, the results indicated that coffee berry can be used as anti-hair loss ingredient in hair care cosmetics.